2015
DOI: 10.1111/mec.13369
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of parasitoid communities of willow‐galling sawflies: habitat overrides physiology, host plant and space

Abstract: Studies on the determinants of plant-herbivore and herbivore-parasitoid associations provide important insights into the origin and maintenance of global and local species richness. If parasitoids are specialists on herbivore niches rather than on herbivore taxa, then alternating escape of herbivores into novel niches and delayed resource tracking by parasitoids could fuel diversification at both trophic levels. We used DNA barcoding to identify parasitoids that attack larvae of seven Pontania sawfly species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 99 publications
0
19
0
Order By: Relevance
“…Our model comparison of host-parasite interactions revealed that most of the turnover is driven by species-specific responses to the environment, impacting species richness, and that co-occurrence was mostly independent. Indeed, a previous study focusing on a subset of the system studied here identified habitat characteristics as the primary drivers of interactions (Nyman et al 2015). We know that interactions vary with the environment in other systems, for instance, herbivory (Shurin et al 2012, Baskett et al 2018) and predation (McKinnon et al 2010, Legagneux et al 2014 are often found to increase with temperature, resulting in spatial variation of trophic cascades (Gray et al 2016).…”
Section: Perspectivesmentioning
confidence: 86%
“…Our model comparison of host-parasite interactions revealed that most of the turnover is driven by species-specific responses to the environment, impacting species richness, and that co-occurrence was mostly independent. Indeed, a previous study focusing on a subset of the system studied here identified habitat characteristics as the primary drivers of interactions (Nyman et al 2015). We know that interactions vary with the environment in other systems, for instance, herbivory (Shurin et al 2012, Baskett et al 2018) and predation (McKinnon et al 2010, Legagneux et al 2014 are often found to increase with temperature, resulting in spatial variation of trophic cascades (Gray et al 2016).…”
Section: Perspectivesmentioning
confidence: 86%
“…By comparing food web structure to phylogenetic signal, we may explore how interacting species coevolve (Nyman et al 2007(Nyman et al , 2015Vazquez et al 2009;Rafferty and Ives 2013;Fontaine and Thébault 2015). As another line of investigation, comparisons of food webs along sites of different glacial or geological history will help us understand the rules for how communities disassemble and reassemble over time (Stone et al 2012).…”
Section: Food Webs As the Defining Objects Of Community Ecologymentioning
confidence: 99%
“…Aggregating units of observation for subsequent analysis is easy, whereas disaggregating them is often impossible". In some cases, we should also be particularly determined in aiming for the highest end of resolution: in particular when asking questions on population-level dynamics, including the potential for indirect interactions such as apparent competition or apparent mutualism (Müller et al 1999;Morris et al 2004Morris et al , 2005van Veen et al 2006;Tack et al 2011), or questions on coevolution and phylogenetic structuring (Nyman et al 2007(Nyman et al , 2015Vazquez et al 2009;Rafferty and Ives 2013;Fontaine and Thébault 2015). Composite taxa may not share the same population dynamics, let alone the same evolutionary trajectories.…”
Section: Food Web Structure Is Affected By Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…They play a central role in the functioning of all terrestrial ecosystems, and the number of species involved is mind‐blowing (Nyman et al . ). Nevertheless, our understanding of the evolutionary and ecological determinants of their diversity is still in its infancy.…”
mentioning
confidence: 97%